2016
DOI: 10.1093/toxsci/kfw026
|View full text |Cite
|
Sign up to set email alerts
|

Moving Toward Integrating Gene Expression Profiling Into High-Throughput Testing: A Gene Expression Biomarker Accurately Predicts Estrogen Receptor α Modulation in a Microarray Compendium

Abstract: Microarray profiling of chemical-induced effects is being increasingly used in medium- and high-throughput formats. Computational methods are described here to identify molecular targets from whole-genome microarray data using as an example the estrogen receptor α (ERα), often modulated by potential endocrine disrupting chemicals. ERα biomarker genes were identified by their consistent expression after exposure to 7 structurally diverse ERα agonists and 3 ERα antagonists in ERα-positive MCF-7 cells. Most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 58 publications
7
76
0
Order By: Relevance
“…However, the high level of accuracy demonstrated the robustness of the computational procedures despite the fact that the biosets were derived from heterogeneous experiments with various exposure conditions carried out in multiple labs. These results are consistent with our past experience in accurately identifying chemical modulators of transcription factors in the mouse liver (Oshida et al, , , ) and MCF‐7 cells (Ryan et al, ). Our approach has a number of advantages compared to other methods used to identify DDI chemicals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the high level of accuracy demonstrated the robustness of the computational procedures despite the fact that the biosets were derived from heterogeneous experiments with various exposure conditions carried out in multiple labs. These results are consistent with our past experience in accurately identifying chemical modulators of transcription factors in the mouse liver (Oshida et al, , , ) and MCF‐7 cells (Ryan et al, ). Our approach has a number of advantages compared to other methods used to identify DDI chemicals.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, in the nCounter data, the cumulative contribution of all genes to the biomarker correlations and resultant P values increased the −Log( P value)s compared to the microarray data. In our earlier studies, we found that removal of groups of genes from the ER biomarker consistently led to lower significance across bioset comparisons (Ryan et al, ). Our conclusion from these studies is that our computational approach is useful to distinguish between DDI and non‐DDI chemicals independent of the platform used to generate the gene expression data.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…For example, some genes overlap between BCScreen and PAM50 [54], the estrogenicity panel [42], and the Tox21 S1500+ panel [31]. This overlap indicates that while the other panels cover some of the biological space in BCScreen, our approach produced a unique gene set.…”
Section: Discussionmentioning
confidence: 97%
“…Studies comparing gene expression signatures of known breast carcinogens with putative non-carcinogens and with carcinogens that don't target the breast can begin to evaluate whether BCScreen can classify chemicals. A similar approach was reported by Ryan et al [42], who developed a consensus gene expression signature for estrogen action, although our expectation is that breast carcinogens act by diverse biological pathways and we designed BCScreen to capture all of them. Another important area of work is to compare gene expression responses among different breast cell and tissue models, including standard cancer cell lines used in high throughput testing and realistic normal human breast tissue models.…”
Section: Discussionmentioning
confidence: 99%